Proceedings of Data Analytics and Management ICDAM 2023, Volume 1 - Swaroop, Abhishek; Polkowski, Zdzislaw; Correia, Sérgio Duarte; Virdee, Bal (Lecture Notes in Networks and Systems, 2024)
XXVI, 695 p. 284 illus., 221 illus. in color.